THE ESSENCE AND STRUCTURE OF FUTURE ELEMENTARY SCHOOL TEACHERS READINESS TO USE AUTHORIAL TECHNOLOGIES IN PROFESSIONAL ACTIVITY - NOVAK, O. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The article analyzes the current requirements and approaches to elementary school teachers’ training. Particular attention is paid to a nature and a structure of future elementary school teachers’ readiness to use authorial technologies in profession actvity. The article provides an author’s own interpretation of the phenomenon of "future elementary school teachers’s readiness to use authorial technologies." It is proven that the future elementary school teachers’ readiness to use authorial technologies is an integrant of their readiness for innovation in the structure of motivational orientation, content-operational and evaluative- reflective components. It is noted in the article that future elementary school teachers’ readiness to use authorial technologies should be considered from the perspective of personal approach.